Plasma Betaine Is Positively Associated with Developmental Outcomes in Healthy Toddlers at Age 2 Years Who Are Not Meeting the Recommended Adequate Intake for Dietary Choline. Issue 8 (9th July 2018) - Wiedeman, Alejandra M; Chau, Cecil M Y; Grunau, Ruth E; McCarthy, Deanna; Yurko-Mauro, Karin; Dyer, Roger A; Innis, Sheila M; Devlin, Angela M
Abstract: Background: Choline is an important nutrient during development. However, there are limited data on dietary choline intake and status in toddlers and the relation to neurodevelopmental outcomes. Objective: This study assessed dietary choline intake and status in healthy toddlers at ages 1 and 2 y and determined the relation to neurodevelopmental outcomes. Methods: This is a secondary analysis of data from healthy toddlers enrolled in a double-blind, randomized controlled trial of long-chain polyunsaturated fatty acid supplementation between ages 1 and 2 y. Dietary intakes of betaine and choline were estimated by 3-d food records; plasma free choline, betaine, and dimethylglycine were quantified by liquid chromatography–tandem mass spectrometry. Developmental outcomes were assessed at age 2 y with the use of the Bayley Scales of Infant and Toddler Development, 3rd edition (Bayley-III), Cognitive and Language composites, and the Beery-Buktenica Developmental Test of Visual–Motor Integration (Beery-VMI). Results: The mean ± SD daily intake for total choline at age 1 y was 174 ± 56.2 mg/d and increased ( P  < 0.001) to 205 ± 67.5 mg/d at age 2 y. At ages 1 and 2 y, 71.8% and 55.8%, respectively, of toddlers did not meet the recommended 200-mg/d Adequate Intake (AI) for dietary choline. At age 1 y, mean ± SD plasma free choline, betaine, and dimethylglycine concentrations were 10.4 ± 3.3, 41.1 ± 15.4, and 4.1 ± 1.9 µmol/L, respectively. Plasma free choline (8.5 ± 2.3 µmol/L) and dimethylglycine (3.2 ± 1.3 µmol/L) concentrations were lower ( P  < 0.001) at age 2 y. Plasma betaine concentrations were positively associated with the Beery-VMI (β = 0.270; 95% CI: 0.026, 0.513; P  = 0.03) at age 2 y. Conclusions: These findings suggest that most toddlers are not meeting the recommended AI for dietary choline and that higher plasma betaine concentrations are associated with better visual-motor development at age 2 y. Further work is required to investigate choline metabolism and its role in neurodevelopment in toddlers. The trial is registered at clinicaltrials.gov as NCT01263912.